Attenuated response of L-type calcium current to nitric oxide in atrial fibrillation - Rozmaritsa, Nadiia (Oxford University Press, 2014)
AIM: Nitric oxide (NO) synthesized by cardiomyocytes plays an important role in the regulation of cardiac function. Here, we studied the impact of NO signalling on calcium influx in human right atrial myocytes and its relation to atrial fibrillation (AF). METHODS AND RESULTS: Right atrial appendages (RAAs) were obtained from patients in sinus rhythm (SR) and AF. The biotin-switch technique was used to evaluate endogenous S-nitrosylation of the α(1C) subunit of L-type calcium channels. Comparing SR to AF, S-nitrosylation of Ca(2+) channels was similar. Direct effects of the NO donor S-nitroso-N-acetyl-penicillamine (SNAP) on L-type calcium current (I(Ca,L)) were studied in cardiomyocytes with standard voltage-clamp techniques. In SR, I(Ca,L) increased with SNAP (100 µM) by 48%, n/N = 117/56, P < 0.001. The SNAP effect on I(Ca,L) involved activation of soluble guanylate cyclase and protein kinase A. Specific inhibition of phosphodiesterase (PDE)3 with cilostamide (1 µM) enhanced I(Ca,L) to a similar extent as SNAP. However, when cAMP was elevated by PDE3 inhibition or β-adrenoceptor stimulation, SNAP reduced I(Ca,L), pointing to cGMP–cAMP cross-regulation. In AF, the stimulatory effect of SNAP on I(Ca,L) was attenuated, while its inhibitory effect on isoprenaline- or cilostamide-stimulated current was preserved. cGMP elevation with SNAP was comparable between the SR and AF group. Moreover, the expression of PDE3 and soluble guanylate cyclase was not reduced in AF. CONCLUSION: NO exerts dual effects on I(Ca,L) in SR with an increase of basal and inhibition of cAMP-stimulated current, and in AF NO inhibits only stimulated I(Ca,L). We conclude that in AF, cGMP regulation of PDE2 is preserved, but regulation of PDE3 is lost.